Meningkatkan Kemampuan Literasi Informasi Mahasiswa dengan Pembentukan Academic Information Literacy Class di Perpustakaan Universitas Riau - Evi Susanti; Thamrin Hasan (Perpustakaan Universitas Riau, 2026)
Technological developments and the penetration of Artificial Intelligence (AI) have triggered the phenomenon of information overload and information anxiety among students. On the other hand, the utilization of digital assets at the University of Riau Library is still relatively low, thus triggering low-quality references and a high risk of plagiarism in student scientific papers. This study aims to describe the design, implementation strategy, and core materials of the